(untitled) (Journal of Science-Innovative Research in Uzbekistan, 2025)
Translating idioms from English into Uzbek is one of the most challenging areas in translation studies, as idioms are deeply rooted in the culture, history, and worldview of a particular language community. Unlike ordinary vocabulary, idiomatic expressions often carry figurative meanings that cannot be understood through direct translation of individual words. For example, the English idiom “kick the bucket” cannot be translated literally into Uzbek (chelakni tepmoq), as this would cause misunderstanding; instead, it requires a cultural or functional equivalent such as “vafot etmoq”.